Danggui-Shaoyao-San Attenuates Cognitive Impairment via the Microbiota–Gut–Brain Axis With Regulation of Lipid Metabolism in Scopolamine-Induced Amnesia - Liu, Piaoxue; Zhou, Xun; Zhang, Haoran; Wang, Rui; Wu, Xiaolang; Jian, Wenxuan; Li, Weirong; Yuan, Dongsheng; Wang, Qi; Zhao, Wei (Frontiers in Immunology, 2022)
Danggui-Shaoyao-San (DSS) has a long history of being used as a traditional medicine (TCM) and has been reported to show therapeutic effects in alleviating the symptoms of cognitive impairment. The purpose of this study was to investigate whether DSS treatment attenuates cognitive impairment via the microbiota–gut–brain axis in scopolamine-induced amnesia. In this work, we first performed the Morris water maze (MWM) test and novel object recognition (NOR) test to evaluate the memory function of treated C57BL/6N mice. Then we evaluated 16S rRNA for gut microbiota analysis, as well as assessment of blood–brain barrier function and intestinal barrier function and lipid metabolism analysis on tissues from different groups. We hypothesised that DSS may affect brain function and behavior through the gut–brain axis in a bidirectional interplay with both top-down and bottom-up regulation. Furthermore, in order to confirm whether intestinal flora plays a crucial role in scopolamine-induced amnesia, C57BL/6N mice were treated with fecal microbial transplantation (FMT), and then behavioral tests were performed. The mice’s feces were simultaneously evaluated by 16S rRNA analysis. The result supported that the FMT-induced improvement in cognitive function highlights the role of the gut microbiota–brain axis to mediate cognitive function and behavior. Besides theses works, more findings indicated that DSS altered lipid metabolism by activating LXR-PPAR-γ and repaired mucosal barrier dysfunction assessed with a broad range of techniques, which attenuated cognitive impairment via the microbiota–gut–brain axis.